2021
DOI: 10.18805/lr-604
|View full text |Cite
|
Sign up to set email alerts
|

​Effect of Irrigation Regimes and Phosphorus Fertilization on Water-use Efficiency, Phosphorus-agronomic Efficiency and Yield of Grass Pea (Lathyrus sativus L.) Ecotypes

Abstract: Background: Grass pea (Lathyrus sativus L.) is a crop of immense economic significance. It is one of the most resilient to climate changes and to be survival food during drought-triggered famines. Methods: In a field study split factorial experiment based on a randomized complete block design with 3 replications were used, effects of irrigation regimes (50, 75 and 100% evaporation of Pan class A) and different rates of phosphorous fertilizer (triple superphosphate 0, 60 and 120 kg/ha) on growth and yield of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The amount of water per plot using water cubic meters per hectare (m 3 water ha -1 ) and the level of each plot is specified and each treatment was provided using a discharge tube (Bahramnejad et al, 2021). Irrigation of each plot was done by drip and using standard tape.…”
Section: Irrigation Schedulingmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of water per plot using water cubic meters per hectare (m 3 water ha -1 ) and the level of each plot is specified and each treatment was provided using a discharge tube (Bahramnejad et al, 2021). Irrigation of each plot was done by drip and using standard tape.…”
Section: Irrigation Schedulingmentioning
confidence: 99%
“…The final performance of each crop plant genotype is determined by the mutual effects of the plant genotype and the growing environment. Bahramnejad et al (2021) reported drought stress by 50% of irrigation water reduces the yield of Lathyrus sativus L. Under drought stress, the reduction in photosynthesis is due to the increase of free rad icals in the plant and the destruction of the photosynthetic system (Liu et al, 2015;Mouradi et al, 2016;Zegaoui et al, 2017) Effect of Different Irrigation Regimes on the Yield and Qualitative Characteristics of Different Cultivars of Soybean (Glycine max...…”
Section: Seed Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Studied the effects of drought stress and phosphorus on grass pea (Lathyrus sativus L.), the use of phosphorus fertilizer (60 kg/ha) increased the yield of grass pea (2401 kg/ha). This means that phosphorus fertilizer can partially compensate for the effect of drought stress and highly impacts water use and phosphorus agronomic efficiency Bahramnejad et al (2021).…”
Section: Introductionmentioning
confidence: 99%